Pesan Moral dalam Syair Nandong Kabupaten Simeulue - Lestina Lestina; Syahriandi Syahriandi; Rasyimah Rasyimah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the moral message in Nandong poetry Simeulue regency. The method used is descriptive qualitative. The data collection technique in this research is observation, interview, note-taking and listening techniques.The data used in this research are fragments of Nandong poetry which contain moral messages in Nandong poetry, Simeulue regency. The data source for this research is the word of Nandong poetry. Simeulue Regency. Data source for this research is the sound of Nandong poetry, Simeulue Regency. Data analysis in this research is data reduction, data presentation, and conclusions or verification. Based on the research results, 31 pieces of moral messages were found in Nandong poetry, Simeulue regency. The moral messages in Nandong poetry, Simeulue regency are divided into 3 types of moral messages. (1) Individual moral messages (8 data of human relationship with themselves), (2) Social moral messages (15 data of human relationship with other human), (3) Religious moral messages (8 data of human relationship with God).